Skrining dan Edukasi Sebagai Upaya Pengendalian Hipertensi - Jamaica, Putri Avanny; Rindarwati, Asti Yunia; Destiani, Dika Pramita; Salsabila, Lyansaputri (Jurnal Pengembangan dan Pengabdian Masyarakat Multikultural, 2024)
Hypertension poses significant global challenges and contributes to the rising morbidity and mortality rates associated with cardiovascular diseases, including heart disease and stroke. Commonly referred to as a "silent killer," hypertension frequently presents without significant symptoms, making early detection and appropriate management crucial. This community service program aims to conduct hypertension screening and provide education to enhance awareness and promote preventive measures. The activities were carried out at a integrated service post (Posyandu), involving 62 participants aged between 34 and 81 years. The program included health screenings, which assessed blood pressure and blood glucose levels, as well as educational sessions addressing hypertension risk factors, preventive strategies, and the importance of therapy adherence. Results indicated that 14.5% of participants had normal blood pressure, while 63% fell into the prehypertensive category, 17.7% were classified as stage 1 hypertension, and 4.8% were identified as having stage 2 hypertension. The educational sessions emphasized lifestyle changes and the importance of regular health monitoring to prevent further complications. This program underscores the necessity of continuous health education and promotion in the community to control hypertension and improve overall public health.